2021
DOI: 10.1292/jvms.20-0679
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Crandell-Rees Feline Kidney cell proliferation by X-ray-induced senescence

Abstract: Radioresistance and radiotoxicity have been reported following cancer treatments in felines. Optimizing radiation doses to induce cytotoxic effects to only cancer cells and not normal cells is critical in achieving effective radiation therapy; however, the mechanisms of radiation resistance, radiotoxicity, and DNA damage response (DDR) in feline cells have not yet been elucidated. A DNA double-strand break (DSB) is the most toxic type of DNA damage induced by X-rays and heavy ion beams used in treating cancers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 35 publications
(56 reference statements)
0
5
0
Order By: Relevance
“…Trypan blue exclusion test was used to determine the number of viable cells in accordance with our previously described methods [ 23 ] with the following modifications. For the radiation toxicity assay, cells were seeded at a density of 5.0 × 10 4 cells per 60-mm dish.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Trypan blue exclusion test was used to determine the number of viable cells in accordance with our previously described methods [ 23 ] with the following modifications. For the radiation toxicity assay, cells were seeded at a density of 5.0 × 10 4 cells per 60-mm dish.…”
Section: Methodsmentioning
confidence: 99%
“…Nuclei were stained with 0.025 μg/mL of 4,6-diamino-2-phenylindole (DAPI) fluorescent dye (Boehringer Mannheim, Mannheim, Germany), in accordance with our previously described methods [ 15 , 23 ]. Images of cells were obtained using an Olympus Fluorescence Microscope BX51 equipped with a digital camera Olympus DP50.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…With similar pathologic findings to humans ( 216 , 217 ), they represent a naturally occurring model for study of senotherapeutics ( 215 ). In vitro studies utilizing feline renal cells have shown a dose dependent correlation with radiation and SC ( 218 ). Further studies can utilize this data to understand the etiopathology of radiotoxicity induced renal senescence and investigation of senotherapeutics in vivo in this context ( Figure 4 ).…”
Section: Senotherapeutic Potential In Veterinary Speciesmentioning
confidence: 99%
“…As the kidney is a target organ of MMI-induced toxicity, an immortalized cell line derived from the renal cortex of a normal cat (CRFK) was used [ 25 ]. Although uncertainty has been suggested about the epithelial vs. mesenchymal phenotype of CRFK cells [ 26 ], they have been originally described as epithelial [ 25 ], and they are widely used accordingly [ 27 , 28 ].…”
Section: Introductionmentioning
confidence: 99%